A prototype of automatic mattress turning device for pressure ulcer prevention - Narongrat Sawattikanon; Kanyaluck Uttrarachon; Radom Pongvuthithum; Thawan Sucharitakul; Wetchayan Rangsri (Journal of Associated Medical Sciences, 2018)
Background: Pressure ulcer is a major health care problem in bed ridden patients. One of preventive measures is repositioning every 2 hours which is a burden workload on a caregiver.